Product Idea Innovation Showcase (PRIDE) 2019 - Idris, Juferi (UiTM Sarawak, 2020)
Product Idea Innovation Showcase (PRIDE) 2019 was held at Dewan Ruai Penggawa, UiTM Cawangan Sarawak, Kampus Samarahan 1 on 14th June 2019. This showcase is a collaboration between Tunas Mekar and Malaysian Academy of SME & Entrepreneurship Development (MASMED), UiTM Sarawak. The objective of this showcase was to provide a platform for students who took Entrepreneurship Course (ENT600) to invent a new product or an idea based on the knowledge they gained throughout the semester which has potential for further commercialization.